2014
DOI: 10.1111/jomf.12075
|View full text |Cite
|
Sign up to set email alerts
|

Proceed With Caution? Parents' Union Dissolution and Children's Educational Achievement

Abstract: Using high-quality Norwegian register data on 49,879 children from 23,655 families, the authors estimated sibling fixed-effects models to explore whether children who are younger at the time of a parental union dissolution perform less well academically, as measured by their grades at age 16, than their older siblings who have spent more time living with both biological parents. Results from a baseline model suggest a positive age gradient that is consistent with findings in some of the extant family structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 59 publications
1
49
3
2
Order By: Relevance
“…Yet as discussed above, conceptual thought of what effects can be estimated with different methods and what effects are of most theoretical interest has not necessarily kept up with the methodological advances (for exceptions: Manski et al 1992;Ní Bhrolcháin 2001;Sigle-Rushton et al 2014). Using parental separation as our example, we distinguished between the effects of separations as events and separations as processes, as well as between the experience of separation and its timing.…”
Section: Discussion and Recommendations For Future Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet as discussed above, conceptual thought of what effects can be estimated with different methods and what effects are of most theoretical interest has not necessarily kept up with the methodological advances (for exceptions: Manski et al 1992;Ní Bhrolcháin 2001;Sigle-Rushton et al 2014). Using parental separation as our example, we distinguished between the effects of separations as events and separations as processes, as well as between the experience of separation and its timing.…”
Section: Discussion and Recommendations For Future Researchmentioning
confidence: 99%
“…Some SFE studies found no effects of parental separation or other family forms on educational outcomes (Björklund and Sundström 2006). Others have found a weak to moderate negative effect on various outcomes even in an SFE design (e.g., Ermisch et al 2004;Sandefur and Wells 1999;Sigle-Rushton et al 2014;Grätz 2015).…”
Section: Sibling Fixed Effectsmentioning
confidence: 99%
See 3 more Smart Citations